2012
DOI: 10.1099/mic.0.056796-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome mining reveals the presence of a conserved gene cluster for the biosynthesis of ergot alkaloid precursors in the fungal family Arthrodermataceae

Abstract: Genome sequence analysis of different fungi of the family Arthrodermataceae revealed the presence of a gene cluster consisting of five genes with high sequence similarity to those involved in the early common steps of ergot alkaloid biosynthesis in Aspergillus fumigatus and Claviceps purpurea. To provide evidence that this cluster is involved in ergot alkaloid biosynthesis, the gene ARB_04646 of the fungus Arthroderma benhamiae was cloned into pQE60 and expressed in Escherichia coli. Enzyme assays with the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
0
19
0
2
Order By: Relevance
“…Interestingly, the uncharacterized PKS-encoding gene on chromosome I (AFUA_1g17740) as well as one of the uncharacterized PKS-encoding gene on chromosome III (AfuA_3g14700) and additional five genes from the same cluster (AFUA_3g14710, 14740, 14750; 14760, and 14770) were only found to be up-regulated comparing the OE:: hasA strain to OE:: hasA /Δ hasD , in which neither HAS nor any intermediate is produced (Table 1 ). Similarly, three ( fgaPT1 / easL, fgaDH / easD , and fgaP450-2 / easM ) of the 11 characterized genes from the fumigaclavine gene cluster (Unsold and Li, 2006 ; Wallwey et al, 2010 ; Robinson and Panaccione, 2012 ; Wallwey et al, 2012 ) as well as one uncharacterized NRPS-encoding gene [AFUA_3g13730; nrps6 / pesG ; (Cramer et al, 2006b ; Stack et al, 2007 )] were only found to be up-regulated when comparing OE:: hasA to OE:: hasA /Δ hasD (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the uncharacterized PKS-encoding gene on chromosome I (AFUA_1g17740) as well as one of the uncharacterized PKS-encoding gene on chromosome III (AfuA_3g14700) and additional five genes from the same cluster (AFUA_3g14710, 14740, 14750; 14760, and 14770) were only found to be up-regulated comparing the OE:: hasA strain to OE:: hasA /Δ hasD , in which neither HAS nor any intermediate is produced (Table 1 ). Similarly, three ( fgaPT1 / easL, fgaDH / easD , and fgaP450-2 / easM ) of the 11 characterized genes from the fumigaclavine gene cluster (Unsold and Li, 2006 ; Wallwey et al, 2010 ; Robinson and Panaccione, 2012 ; Wallwey et al, 2012 ) as well as one uncharacterized NRPS-encoding gene [AFUA_3g13730; nrps6 / pesG ; (Cramer et al, 2006b ; Stack et al, 2007 )] were only found to be up-regulated when comparing OE:: hasA to OE:: hasA /Δ hasD (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ergot alkaloids are known from diverse members of the Pezizomycotina (filamentous ascomycetes) (Marcet-Houben and Gabaldón 2016; Wallwey et al 2012). In addition to the family Clavicipitaceae (order Hypocreales), clavines and other ergot alkaloids have been isolated from some Penicillium, Aspergillus, and Neosartorya species (Trichocomaceae, Eurotiales), and from a Dicyma species (Xylariaceae, Xylariales).…”
Section: Sources Of Ergot Alkaloidsmentioning
confidence: 99%
“…The gene ARB_04646 in Arthroderma benhamiae was expressed in E. coli, and the results showed that the encoded enzyme catalyzed the oxidation of chanoclavine-I in the presence of NAD + , resulting in the formation of chanoclavine-I aldehyde. 59 Thus, this gene as the homologous gene of easD and fgaDH also functioned as the oxidoreductase. At the present time, the four reactions described above constitute the common biosynthetic pathway of ergot alkaloids in different fungal species (Fig.…”
Section: Common Biosynthetic Pathway Towards Chanoclavine-ialdehydementioning
confidence: 99%